Romania : Urban Sector Rapid Assessment - World Bank (Washington, DC, 2014)
Cities have long held a central place of importance in society as hubs of commerce, culture, and political power. Because of climate change, however, the clustering together of large numbers of people and high levels of economic activity also creates vulnerabilities. In Romania, where the urbanization rate is roughly 55 percent, the Government of Romania has commissioned this advisory services report from the World Bank to explore how to operationalize an urban climate strategy within the structure of the European Union's new 2014-2020 operating program. This report presents the results for the rapid assessment of the current state of (and opportunities for improved) urban climate planning in Romania; what is known about how cities in Romania contribute to climate change; and how cities in Romania will be affected by climate change. To complete this rapid assessment, the World Bank team relied on an extensive literature review and in-person, semi-structured interviews with more than two dozen central and local government officials, private sector experts, academics, and civil society organizations knowledgeable about climate change topics in Romania. The depth of this rapid assessment was necessarily limited by the short time frame available to carry out the research, and by data gaps on local climate planning activities, local greenhouse gas (GHG) emission levels, and the climate risks faced by cities around Romania.